Structure and rheology of self-assembled aqueous suspensions of nanoparticles and wormlike micelles. Issue 6 (13th April 2018) - Sambasivam, Abhinanden; Dhakal, Subas; Sureshkumar, Radhakrishna
Abstract: We present a systematic molecular dynamics (MD) simulation study of the structure and rheology of solutions consisting of cationic micelles and negatively charged nanoparticles (NPs) in the presence of a hydrotropic salt, namely, sodium salicylate. The addition of NPs to wormlike micelle (WLM) solutions results in the formation of electrostatically stabilised NP-micelle junctions, leading to a significant enhancement in the viscosity of the mixture due to effective lengthening of micelle clusters. A monotonic increase in zero-shear viscosity is observed as the NP volume fraction is increased. Branched micelles form at sufficiently large salt concentrations. Sliding motion of micelle branches along the contour of a wormlike chain provides an additional mechanism for stress relaxation. Hence, branch formation induces a non-monotonic variation in the solution viscosity as a function of the salt concentration. Reverse non-equilibrium MD simulations were performed to study the effect of uniform and steady shear flow on the viscosity of the WLM-NP mixtures. Beyond a critical shear rate, flow-induced anisotropy, which is quantified by an orientational order parameter, manifests as viscoelastic rheological behaviour. Specifically, at higher NP volume fractions and shear rates that exceed the inverse of a characteristic structure relaxation time, flow-alignment of the microstructure causes pronounced shear thinning.